PHARMACOKINETIC AND PHARMACODYNAMIC INTERACTION OF MULTIPLE DOSE MANGOSTEEN RIND EXTRACT AND METFORMIN IN ALLOXAN-INDUCED DIABETIC RATS - Fanny
Diabetes Mellitus 9DM) is a metabolic disorder characterized by hyperglycemia. WHO has reported that diabetes was the cause of 1.6 million death in 2015. Many patients who suffered from diabetes used herbs as a complementary or alternative medicine. Previous studies have shown antihyperglycemic activity of mangosteen rind extract (EM) containing ?-mangostin (AM). The aim of this research was to evaluate pharmacokinetic and pharmacodynamic interaction of multiple dose combination of EM and MFN. This research was performed on alloxan-induced diabetic Wistar rats. EM was given at a dose of 248 mg/kg BW and MFN was given at a dose of 100 mg/kg BW as multiple doses for 14 days. The study was performed in 4 groups, which received MFN, combination EM and MFN, normal control dan DM control, respectively. AM and MFN concentrations in plasma were determined by HPLC. Plasma glucose levels were measured by GOD-PAP method. Pharmacokinetic parameters of AM and MFN and AAC values were calculated. Single dose combination of EM dan MFN (AAC 2895.75 mg.h/dL) showed higher antihyperglycemic effect when compared to multiple dose combination of EM and MFN (AAC 2131.78 mg.h/dL). EM 14 days decreased AUC0-12 MFN 14 days by 50.86%. The combination of multiple dose EM and MFN reduced AUC0-12 and Cmax 49.83% and 40.89% compared to single dose MFN, respectively. Pancreatic histology which showed the best pancreatic beta cell repair were EM 14 days followed by AM 14 days, (EM-MFN) 14 days and MFN 14 days respectively.